Positive electrode sheet and lithium ion battery
By adopting a double-layer design in the positive electrode sheet of the lithium-ion battery, the first active material layer with high binder content and the second active material layer with low binder content, the problem of energy density loss in the lithium-ion battery when improving safety performance is solved, and the effect of significantly improving the safety performance and energy density of nail penetration is achieved.
Patent Information
- Application Number
- CN202210707751.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2018-02-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2038-02-26
AI Technical Summary
While improving safety performance, existing lithium-ion batteries are difficult to maintain a high energy density, and common technical means will cause loss of energy density.
The positive electrode sheet with a double-layer design has a higher adhesive content in the first active material layer than the second active material layer, which not only ensures the energy density of the lithium-ion battery, but also improves the bonding force between the active material layer of the positive electrode sheet and the current collector.
It significantly improves the nail-piercing safety performance of lithium-ion batteries, reduces the risk of short circuit, and improves the safety performance of the battery without significantly losing energy density.
Smart Images

Figure BDA0003706078310000161 
Figure BDA0003706078310000171
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application filed with the China Patent Office on February 26, 2018, with application number 201810163122.0 and invention name “A positive electrode sheet and lithium-ion battery”. Technical Field
[0002] The present application relates to the field of lithium-ion batteries, and more specifically, to a positive electrode sheet and a lithium-ion battery. Background Art
[0003] The market has higher and higher requirements for the safety of lithium-ion batteries. At the same time, lithium-ion batteries are also required to maintain a high energy density. Therefore, it is necessary to introduce corresponding technical elements for improvement. At present, the commonly used technical means to improve the safety of lithium-ion batteries will cause a large loss of energy density. Therefore, it is urgent to provide a technical means that can significantly improve the safety performance of lithium-ion batteries under the condition of higher volume energy density. Summary of the invention
[0004] In order to solve the defect of the prior art that energy density and safety cannot be taken into account at the same time, according to the first aspect of the present application, a positive electrode plate is provided, including: a current collector; a first active material layer; and a second active material layer; wherein the first active material layer is arranged between the current collector and the second active material layer, the first active material layer and the second active material layer both include a binder, and the binder content in the first active material layer is greater than the binder content in the second active material layer.
[0005] In the above-mentioned positive electrode sheet, the first active material layer is formed on at least one surface of the current collector.
[0006] In the above-mentioned positive electrode sheet, the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is 1.1-4.
[0007] In the above-mentioned positive electrode sheet, the weight percentage of the binder in the second active material layer is 0.1% to 5%.
[0008] In the above-mentioned positive electrode plate, the binder is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and fluorinated olefin, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, fluorinated rubber, polyvinyl alcohol and combinations thereof.
[0009] In the above-mentioned positive electrode sheet, the binder in the first active material layer and the binder in the second active material layer are the same or different.
[0010] In the above-mentioned positive electrode sheet, the first active material layer further includes a positive electrode active material and a conductive agent, and the positive electrode active material includes a combination of one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide. It should be noted that the above positive electrode active materials include positive electrode active materials that have been doped and / or coated in the prior art. The conductive agent is selected from a combination of one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
[0011] In the above-mentioned positive electrode sheet, the second active material layer further includes a positive electrode active material and a conductive agent, and the positive electrode active material includes a combination of one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate. It should be noted that the above positive electrode active materials include positive electrode active materials that have been doped and / or coated in the prior art. The conductive agent is selected from a combination of one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
[0012] According to the second aspect of the present application, a lithium-ion battery is also provided, which includes the positive electrode sheet according to the first aspect of the present application.
[0013] The above lithium-ion battery also includes: an electrolyte, a negative electrode sheet containing a negative electrode active material, and a separator, wherein the negative electrode active material is selected from natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel-structured lithiated TiO2-Li4Ti5O 12 , a combination of one or more of Li-Al alloys.
[0014] In the present application, the active material layer in the positive electrode sheet adopts a double-layer design, and the content of the binder in the first active material layer is higher than that in the second active material layer, which not only ensures the energy density of the lithium-ion battery, but also serves the purpose of improving the bonding force between the active material layer of the positive electrode sheet and the positive current collector. Among them, the high binder content in the first active material layer ensures a strong bonding force between the first active material layer and the aluminum substrate (current collector), and plays a role in that the first active material layer will not be separated from the aluminum substrate during nail penetration, so that the aluminum substrate will not directly contact the negative active material layer on the surface of the negative electrode sheet, thereby reducing the short circuit risk during nail penetration, and ultimately improving the nail penetration safety performance of the lithium-ion battery; and the low binder content in the second active material layer can ensure the overall compaction density of the electrode sheet and the positive active material content in the second active material layer, and ensure the energy density.
[0015] In addition, the positive electrode sheet provided by the present application can significantly improve the safety performance of lithium-ion batteries, which is specifically manifested in significantly improving the pass rate of lithium-ion batteries in nail penetration tests. When the positive electrode sheet including the first active material layer and the second active material layer is applied to a lithium-ion battery, the first active material layer changes the short-circuit mode of the lithium-ion battery during nail penetration, from the short-circuit mode of the positive current collector (aluminum substrate)-negative active material layer to the short-circuit mode of the positive active material layer-negative active material layer. Under the action of the first active material layer, the short-circuit heat generation power of the lithium-ion battery during nail penetration can be significantly reduced, thereby greatly improving the safety performance of the lithium-ion battery. DETAILED DESCRIPTION
[0016] The exemplary embodiments are described in detail below, but these exemplary embodiments can be implemented in different ways and should not be interpreted as being limited to the embodiments described in this application. On the contrary, the purpose of providing these embodiments is to make the disclosure of this application thorough and complete, and to fully convey the scope of this application to those skilled in the art.
[0017] The present application provides a positive electrode plate design, which can significantly improve the safety performance of lithium-ion batteries, specifically by significantly improving the pass rate of lithium-ion batteries in nail penetration tests.
[0018] According to the first aspect of the present application, the present application provides a positive electrode sheet, comprising: a current collector; a first active material layer; and a second active material layer; wherein the first active material layer is arranged between the current collector and the second active material layer, the first active material layer and the second active material layer both include a binder, and the binder content in the first active material layer is greater than the binder content in the second active material layer.
[0019] The first active material layer is formed on at least one surface of the current collector, that is, the first active material layer may be formed on one surface of the current collector, or may be formed on both surfaces of the current collector at the same time.
[0020] In the positive electrode sheet according to the first aspect of the present application, the content of the binder in the first active material layer is higher than the content of the binder in the second active material layer, which not only ensures the energy density of the lithium-ion battery, but also serves the purpose of improving the bonding force between the active material layer of the positive electrode sheet and the positive current collector. Among them, the high binder content in the first active material layer ensures a strong bonding force between the first active material layer and the aluminum substrate (current collector), and plays a role in that the first active material layer will not be separated from the aluminum substrate during nail penetration, so that the aluminum substrate will not directly contact the negative active material layer on the surface of the negative electrode sheet, thereby reducing the short circuit risk during nail penetration, and ultimately improving the nail penetration safety performance of the lithium-ion battery; and the low binder content in the second active material layer can ensure the overall compaction density of the electrode sheet and the positive active material content in the second active material layer, and ensure the energy density.
[0021] The active material layer in the traditional positive electrode sheet has a binder content of 3% to 8wt%. The binder content is relatively high. A higher binder content will lead to a decrease in the content of the positive electrode active material, thereby reducing the energy density of the lithium-ion battery. In order to increase the energy density of the lithium-ion battery, reducing the binder content will also lead to a problem of reduced bonding between the positive current collector and the active material layer, resulting in a decrease in the safety performance of the lithium-ion battery. In order to balance these two issues, the present application adopts a double-layer design for the active material layer in the positive electrode sheet, with the first active material layer using a high binder content and the second active material layer using a low binder content, which not only ensures the energy density of the lithium-ion battery, but also improves the nail penetration rate of the lithium-ion battery, and its safety performance is significantly improved.
[0022] According to some embodiments of the present application, the content of the binder in the second active material layer is 0.1% to 5wt%, and the content of the binder in the first active material layer is 1.1 to 4 times the content of the binder in the second active material layer. When the content of the binder in the second active material layer is ≥5wt%, the compaction density of the pole piece is low and the energy density loss is high, so the content of the binder in the second active material layer is selected to be ≤5wt%, and when the content of the binder in the second active material layer is less than 0.1wt%, the mutual bonding of the active materials in the second active material layer and the bonding between the second active material layer and the first active material layer cannot be guaranteed, so the content of the binder in the second active material layer is selected to be ≥0.1wt%.
[0023] When the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is 1.1 to 4, the nail penetration rate gradually improves from 80% to 100%. Although the energy density is reduced, the reduction is not obvious. When the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is less than 1.1, the nail penetration rate is low. When the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is greater than 4, although the bonding force between the first active material layer and the substrate can be significantly improved, the energy density is seriously lost. Therefore, the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is selected to be 1.1 to 4. Among them, within this range, when the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is 1.1 to 1.5, the first active material layer has a higher bonding force, the active material is well bonded to the aluminum substrate, and during the nailing process, the aluminum substrate is adhered by the first active material layer and will not be exposed, thereby avoiding direct contact between the aluminum substrate and the negative active material layer of the negative electrode sheet, thereby improving the nailing, but the improvement effect is limited; when the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is 1.1 to 1.5, the first active material layer has a higher bonding force, the active material is well bonded to the aluminum substrate, and during the nailing process, the aluminum substrate is adhered to the first active material layer and will not be exposed, thereby avoiding direct contact between the aluminum substrate and the negative active material layer of the negative electrode sheet, thereby improving the nailing, but the improvement effect is limited; When the ratio is 1.5-2, the improvement effect is significant, and the nail penetration rate can be increased to 100%; continue to increase the content of the binder in the first active material layer, when the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is 2-4, the nail penetration effect is still significant, which can reach 100%, but the compaction density and energy density are reduced; therefore, when the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is preferably 1.5-2, it can not only ensure the energy density, but also achieve the effect of improving the safety of lithium-ion batteries.
[0024] The binder used in the present application includes at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and fluorinated olefin, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, fluorinated rubber, polyvinyl alcohol, and combinations thereof. The binder in the first active material layer and the binder in the second active material layer may be the same or different.
[0025] In the present application, the first active material layer also includes a positive electrode active material and a conductive agent, the positive electrode active material includes a combination of one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide, and the conductive agent is selected from a combination of one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
[0026] In the present application, the second active material layer also includes a positive electrode active material and a conductive agent, the positive electrode active material includes a combination of one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate, and the conductive agent is selected from a combination of one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
[0027] In the present application, the active material layer in the positive electrode sheet adopts a double-layer design, and the content of the binder in the first active material layer is higher than that in the second active material layer, which not only ensures the energy density of the lithium-ion battery, but also serves the purpose of improving the bonding force between the active material layer of the positive electrode sheet and the positive current collector. When the positive electrode sheet including the first active material layer and the second active material layer is applied to the lithium-ion battery, the first active material layer changes the short-circuit mode of the lithium-ion battery when nailing, from the short-circuit mode of the positive current collector (aluminum substrate)-negative active material layer to the short-circuit mode of the positive active material layer-negative active material layer. Under the action of the first active material layer, the short-circuit heat generation power of the lithium-ion battery when nailing can be significantly reduced, thereby greatly improving the safety performance of the lithium-ion battery.
[0028] According to the second aspect of the present application, the present application provides a lithium-ion battery, which includes the positive electrode plate according to the first aspect of the present application.
[0029] In the lithium-ion battery according to the second aspect of the present application, the lithium-ion battery further includes a negative electrode sheet containing a negative electrode active material, a separator and an electrolyte.
[0030] In the lithium-ion battery according to the second aspect of the present application, the electrolyte may be a lithium hexafluorophosphate electrolyte, and the separator may be polyethylene. The negative electrode active material is selected from natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel-structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or a combination of one or more thereof. However, it should be understood by those skilled in the art that the above-mentioned negative electrode sheet, separator, and electrolyte are merely examples and are not subject to specific limitations. They can be selected according to needs without departing from the contents disclosed in this application.
[0031] The preparation of a lithium-ion battery is described below. The preparation method includes: preparation of a positive electrode sheet, preparation of a negative electrode sheet, preparation of an electrolyte, preparation of a separator, and preparation of a lithium-ion battery, specifically including the following steps:
[0032] Preparation of positive electrode sheet: (1) Mix a positive electrode active material such as lithium cobalt oxide (LiCoO2), nickel cobalt manganese, nickel cobalt aluminum oxide, lithium iron phosphate (LiFePO4), preferably lithium cobalt oxide (LiCoO2), and a conductive agent carbon black (Super P) with a binder polyvinylidene fluoride (the binder content can be adjusted within the range of 0.1-5wt%) in a weight ratio of 90-98:1-2, add N-methylpyrrolidone (NMP), and stir the mixture under the action of a vacuum stirrer until the system becomes a dispersed slurry to obtain an upper positive electrode slurry; (2) Mix a positive electrode active material such as lithium cobalt oxide (LiCoO2), nickel cobalt manganese, nickel cobalt aluminum oxide, lithium iron phosphate (LiFePO4), lithium manganese oxide (LiMn2O4), preferably lithium nickel cobalt manganese oxide, and a conductive agent carbon black (Super P) in a weight ratio of 90-98:1-2. P) mixed with a binder polyvinylidene fluoride (the binder content is 1.1-4 times the binder content in step (1)) in a weight ratio of 95-98:1-2, added with N-methylpyrrolidone (NMP), and stirred under the action of a vacuum stirrer until the system becomes a dispersed slurry to obtain a lower positive electrode slurry; (3) firstly, the lower positive electrode slurry is uniformly coated on the positive electrode current collector aluminum foil to prepare a first active material layer; the first active material layer is dried at 80-90°C, preferably 85°C, and then the upper positive electrode slurry is uniformly coated on the dried first active material layer to prepare a second active material layer; the electrode sheet is dried at 80-90°C, preferably 85°C, and after cold pressing, cutting and slitting, it is dried under vacuum conditions at 85°C for 2-6h, preferably 4h to obtain a positive electrode sheet.
[0033] Negative electrode sheet preparation: Negative electrode active materials such as natural graphite, artificial graphite, mesophase carbon microspheres (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy, preferably artificial graphite negative electrode active material, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), binder styrene butadiene rubber (SBR) are mixed according to a weight ratio of 95-98:1-2:0.1-1:1-2, preferably 96.4:1.5:0.5:1.6, deionized water is added, and a negative electrode slurry is obtained under the action of a vacuum mixer; the negative electrode slurry is evenly coated on the negative electrode collector copper foil; the copper foil is dried at 80-90°C, preferably at 85°C, and then after cold pressing, cutting and slitting, it is dried at 80-90°C, preferably at 80°C under vacuum conditions for 10-14h, preferably 12h, to obtain a negative electrode sheet.
[0034] Electrolyte preparation: Use conventional 1.5M lithium hexafluorophosphate electrolyte.
[0035] Preparation of isolation film: A polyethylene (PE) isolation film substrate with a thickness of 2 to 20 μm, preferably 7 μm, is coated with a 5 μm ceramic coating.
[0036] Preparation of lithium-ion batteries: stack the positive electrode sheet, the separator, and the negative electrode sheet in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wind them to obtain a bare cell; after welding the tabs, place the bare cell in an outer packaging foil aluminum-plastic film, inject the above-prepared electrolyte into the dried bare cell, and obtain a lithium-ion battery after vacuum packaging, standing, formation (charging at a constant current of 0.02C to 3.3V, and then charging at a constant current of 0.1C to 3.6V), shaping, capacity testing and other processes.
[0037] Those skilled in the art will understand that the above-described method for preparing a lithium-ion battery is only an example, and other materials, numerical ranges and methods commonly used in the art may be used without departing from the disclosure of the present application.
[0038] Some specific embodiments and comparative examples are listed below to better illustrate the present application.
[0039] Example 1
[0040] (1) Preparation of positive electrode sheet
[0041] The positive electrode active material lithium cobalt oxide, the conductive agent Super P, and the binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97.6:2.3:0.1, N-methylpyrrolidone (NMP) is added, and the mixture is stirred in a vacuum mixer until the system becomes a uniform slurry to obtain an upper positive electrode slurry;
[0042] The positive electrode active material lithium nickel cobalt manganese oxide, the conductive agent Super P, and the binder polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 96.6:3.2:0.2, N-methylpyrrolidone (NMP) was added, and the mixture was stirred under the action of a vacuum stirrer until the system became a uniform slurry to obtain a lower positive electrode slurry;
[0043] First, the lower layer of positive electrode slurry is evenly coated on the positive electrode collector aluminum foil to prepare the first active material layer; the first active material layer is dried at 85°C, and then the upper layer of positive electrode slurry is evenly coated on the dried first active material layer; the electrode sheet is dried at 85°C, and after cold pressing, cutting and slitting, it is dried under vacuum conditions at 85°C for 4 hours to obtain the positive electrode sheet.
[0044] (2) Negative electrode sheet preparation
[0045] The negative electrode active material artificial graphite, the conductive agent Super P, the thickener sodium carboxymethyl cellulose (CMC), and the binder styrene-butadiene rubber are mixed in a weight ratio of 96.4:1.5:0.5:1.6, deionized water is added, and the mixture is stirred under the action of a vacuum mixer until the system becomes a uniform slurry to obtain a negative electrode slurry; the negative electrode slurry is then evenly coated on the negative electrode current collector copper foil; the copper foil is dried at 85°C, and after cold pressing, cutting and slitting, it is dried under vacuum conditions at 80°C for 12 hours to obtain a negative electrode sheet.
[0046] (3) Preparation of electrolyte
[0047] A conventional 1.5M concentration lithium hexafluorophosphate electrolyte was selected.
[0048] (4) Preparation of isolation film
[0049] A conventional 7 μm thick polyethylene (PE) isolation film substrate is selected to be coated with a 5 μm ceramic coating.
[0050] (5) Preparation of lithium-ion batteries
[0051] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain a bare battery cell; after welding the pole ears, the bare battery cell is placed in an outer packaging aluminum-plastic film, and the prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, a lithium-ion battery is obtained.
[0052] Example 2
[0053] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 0.5wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0054] Example 3
[0055] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 0.8wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0056] Example 4
[0057] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 1.0wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0058] Example 5
[0059] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 1.5wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0060] Example 6
[0061] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0062] Example 7
[0063] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2.5wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0064] Example 8
[0065] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 3wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0066] Example 9
[0067] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 3.5wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0068] Example 10
[0069] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 4wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0070] Embodiment 11
[0071] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 4.5wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0072] Example 12
[0073] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 5wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0074] Example 13
[0075] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 1.1.
[0076] Embodiment 14
[0077] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 1.3.
[0078] Embodiment 15
[0079] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 1.5.
[0080] Example 16
[0081] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.5.
[0082] Embodiment 17
[0083] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 3.
[0084] Embodiment 18
[0085] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 3.5.
[0086] Embodiment 19
[0087] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 4.
[0088] Embodiment 20
[0089] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and polytetrafluoroethylene (PTFE) is used as a binder in the lower positive electrode slurry (corresponding to the first active material layer), and the content of the binder polytetrafluoroethylene (PTFE) in the lower positive electrode slurry is adjusted so that the ratio of the content of polytetrafluoroethylene (PTFE) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0090] Embodiment 21
[0091] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and polyurethane is used as a binder in the lower positive electrode slurry (corresponding to the first active material layer), and the content of the binder polyurethane in the lower positive electrode slurry is adjusted so that the ratio of the content of polyurethane in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0092] Embodiment 22
[0093] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and fluorinated rubber is used as a binder in the lower positive electrode slurry (corresponding to the first active material layer), and the content of the binder fluorinated rubber in the lower positive electrode slurry is adjusted so that the ratio of the content of fluorinated rubber in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0094] Embodiment 23
[0095] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and polyvinyl alcohol is used as a binder in the lower positive electrode slurry (corresponding to the first active material layer), and the content of the binder polyvinylidene fluoride in the lower positive electrode slurry is adjusted so that the ratio of the content of polyvinyl alcohol in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0096] Embodiment 24
[0097] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, polytetrafluoroethylene (PTFE) is used as a binder in the upper positive electrode slurry (corresponding to the second active material layer), the content of the binder polytetrafluoroethylene (PTFE) in the upper positive electrode slurry is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polytetrafluoroethylene (PTFE) in the upper positive electrode slurry is 2.
[0098] Embodiment 25
[0099] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, polyurethane is used as a binder in the upper positive electrode slurry (corresponding to the second active material layer), the content of the binder polyurethane in the upper positive electrode slurry is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyurethane in the upper positive electrode slurry is 2.
[0100] Embodiment 26
[0101] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, fluorinated rubber is used as a binder in the upper positive electrode slurry (corresponding to the second active material layer), the content of the binder fluorinated rubber in the upper positive electrode slurry is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of fluorinated rubber in the upper positive electrode slurry is 2.
[0102] Embodiment 27
[0103] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, polyvinyl alcohol is used as a binder in the upper positive electrode slurry (corresponding to the second active material layer), the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinyl alcohol in the upper positive electrode slurry is 2.
[0104] Comparative Example 1
[0105] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 1.
[0106] Comparative Example 2
[0107] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 2wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 0.8.
[0108] Comparative Example 3
[0109] The preparation methods of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the lithium-ion battery are the same as those in Example 1, except that, in the preparation process of the positive electrode sheet, while keeping the content of the conductive agent SuperP in the upper and lower positive electrode slurries unchanged, the content of the binder polyvinylidene fluoride (PVDF) in the upper positive electrode slurry (corresponding to the second active material layer) is adjusted to 0.08wt%, and the content of the binder polyvinylidene fluoride (PVDF) in the lower positive electrode slurry (corresponding to the first active material layer) is adjusted so that the ratio of the content of polyvinylidene fluoride (PVDF) in the lower positive electrode slurry to the content of polyvinylidene fluoride (PVDF) in the upper positive electrode slurry is 2.
[0110] Performance Test:
[0111] The positive electrode compaction density, energy density, bonding force between the second active material layer and the first active material layer, bonding force between the first active material layer and the positive electrode current collector (aluminum substrate), and 4.4V nail penetration rate of the lithium ion batteries in Examples 1-27 and Comparative Examples 1-3 were tested, and the test method was as follows:
[0112] 1. Nail penetration test method:
[0113] Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 0.5C to a voltage of 4.4V, and then charge it at a constant voltage of 4.4V to a current of 0.025C. Transfer the fully charged lithium-ion battery to the nail penetration tester, maintain the test environment temperature at 25℃±2℃, and use a steel nail with a diameter of 4mm to uniformly penetrate the center of the lithium-ion battery at a speed of 30mm / s. Keep it for 300s, and the lithium-ion battery will pass if it does not catch fire or explode. Test 10 lithium-ion batteries each time, and the number of lithium-ion batteries that pass the nail penetration test is used as an indicator to evaluate the safety performance of lithium-ion batteries.
[0114] 2. Volume energy density test method:
[0115] Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 0.5C to a voltage of 4.4V, then charge it at a constant voltage of 4.4V to a current of 0.05C, and discharge it at 0.5C to a voltage of 3.0V, and record the discharge energy.
[0116] Volume energy density = discharge energy / (lithium-ion battery length*width*thickness); where length, width, and thickness refer to the length, width, and thickness of the packaged lithium-ion battery.
[0117] 3. Measurement method of compaction density (PD): Take the positive electrode sheet (including the positive electrode current collector and the positive electrode active material layer, the same below) after cold pressing, and use 1540.25mm 2 6 positive electrode sheets and 6 positive electrode current collectors were punched out from the mold. The total weight of the 6 positive electrode sheets was Mc g and the total weight of the 6 positive electrode current collectors was Mag using an analytical balance (Shanghai Jingke Tianmei Electronic Balance FA2004B). The average thickness of the 6 positive electrode sheets was T1 mm and the average thickness of the 6 positive electrode current collectors was T2 mm using a micrometer (Japan Mitutoyo micrometer 293-230). Then PD = [(Mc-Ma) / 6] / (T1-T2) / 1540.25*1000, g / cm 3 (g / cc).
[0118] 4. Adhesion test method
[0119] 1) Take the positive electrode to be tested and use a blade to cut a sample with a width of 30mm and a length of 100-160mm.
[0120] 2) Stick NITTO 5000NS double-sided tape on a steel plate with a width of 30mm and a length of 200-300mm. The double-sided tape has a width of 20mm and a length of 90-150mm.
[0121] 3) Stick the positive electrode sample cut in step 1) on the double-sided tape with the test side facing down.
[0122] 4) Fix the paper tape with the same width as the positive electrode sheet and 80-200 mm longer than the sample length with crepe glue.
[0123] 5) Fold the paper tape upwards, fix it with the upper clamp, and test its bonding strength with a high-speed AI-3000 tensile testing machine, with a tensile speed of 50 mm / min and a tensile displacement of 50 mm.
[0124] 6) Take the tensile force value f when the curve is flat and the displacement is greater than 10mm to calculate the bonding force, F = f*g (9.8N / kg) / 0.02 (positive electrode sheet width), unit: N / m.
[0125] 7) Test of adhesion of the first active material layer: After coating the positive electrode current collector with the lower positive electrode slurry, the test is performed using the above steps 1) to 6).
[0126] 8) Second active material layer adhesion test: After coating the electrode sheet with the upper positive electrode slurry, perform the test using the above steps 1) to 6).
[0127] 9) Test of adhesion of first active material layer + second active material layer: The active material layer is tested using the above steps 1) to 6). After the electrode is stretched, it will peel off at the location with smaller adhesion. When the substrate is exposed after peeling, the adhesion of the first active material layer is less than the adhesion of the second active material layer. When the first active material layer is retained after peeling, the adhesion of the first active material layer is greater than the adhesion of the second active material layer.
[0128] 10) Post-capacity wet film adhesion test method: disassemble the post-capacity lithium-ion battery in a drying room, take out the cathode electrode, spread the electrode and air-dry it for 4 hours, and use methods 1) to 6) for testing. After the electrode is stretched, it will peel off at the place with smaller adhesion. When the substrate is exposed after peeling, the adhesion of the first active material layer is less than the adhesion of the second active material layer; when the first active material layer is retained after peeling, the adhesion of the first active material layer is greater than the adhesion of the second active material layer.
[0129] The measurement results of various embodiments and comparative examples are shown in the following Table 1. For the convenience of comparison, the results of Table 1 are shown in groups, and the results of Example 6 are shown in different groups.
[0130] Table 1
[0131]
[0132]
[0133] From Table 1, we can draw the following conclusions by comparison:
[0134] 1. According to Comparative Examples 1 and 2 and Examples 6 and 13-27, when the binder content in the first active material layer of the positive electrode is greater than the binder content in the second active material layer, although the energy density is reduced, the nail penetration rate is effectively improved.
[0135] 2. According to Comparative Example 3 and Examples 1-12, when the binder content in the second active material layer of the positive electrode sheet is greater than 0.1 wt%, the nail penetration rate gradually increases.
[0136] 3. According to Examples 5 to 12, in a double-layer design, the bonding force of the second active material layer has little effect on the improvement of nail penetration, and increasing the binder content will result in a loss of energy density.
[0137] 4. According to Examples 5-12, in the double-layer design of the positive electrode plate, when the binder content in the first active material layer is 3wt%, the bonding force is equal to 80N / m, and the nail penetration rate is 10 / 10. Although the bonding force increases by continuing to increase the binder content in the first active material layer, a certain energy density will be lost.
[0138] 5. When the bonding force in the first active material layer is greater than a certain value, the nail penetration effect is significantly improved. When the binder content in the first active material layer is 3wt%, the bonding force is equal to 80N / m, and the nail penetration rate is 10 / 10. When the binder content in the second active material layer is selected from 1% to 3wt%, the energy density is reduced, but not significantly. Continuing to increase the binder content in the first active material layer or the second active material layer will lose a certain amount of energy density.
[0139] 6. According to Examples 6 and 20-27, it was found that the type of binder in the first active material layer and the second active material layer has a certain influence on the energy density of the lithium-ion battery, but has no significant effect on the nail penetration rate. When polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE) are used as binders, the energy density and compaction density are significantly higher than when other substances are used as binders.
[0140] 7. When the binder content in the second active material layer is ≥3wt%, the compaction density of the pole piece is low, and the energy density is lost. Therefore, when the binder content in the second active material layer is selected to be ≤3wt%, when the ratio of the binder content in the first active material layer to the binder content in the second active material layer is 1.1-1.5, the first active material layer has a higher bonding force, and the active material is well bonded to the aluminum substrate. During the nailing process, the aluminum substrate is protected by the first active material layer and will not be exposed, thereby avoiding direct contact between the aluminum substrate and the negative active material layer on the surface of the negative electrode piece. Therefore, it plays a role in improving nailing, but the improvement effect is limited; when the first When the ratio of the content of the binder in the active material layer to the content of the binder in the second active material layer is 1.5-2, the improvement effect is significant, and the nail penetration rate can be increased to 100%; continue to increase the content of the binder in the first active material layer, when the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is 2-4, the nail penetration effect is still significant, which can reach 100%, but the compaction density and energy density are reduced; therefore, when the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is preferably 1.5-2, it can not only ensure the energy density, but also achieve the effect of improving the safety of lithium-ion batteries.
[0141] Those skilled in the art should understand that the above embodiments are merely exemplary embodiments and that various changes, substitutions and alterations may be made without departing from the spirit and scope of the present application.
Claims
1. A lithium-ion battery, comprising a positive electrode sheet and a negative electrode sheet containing a negative electrode active material, wherein the positive electrode sheet comprises: A current collector, wherein the current collector is an aluminum substrate; a first active material layer; as well as a second active material layer; The first active material layer is arranged between the current collector and the second active material layer, the first active material layer is formed on both surfaces of the current collector, the first active material layer and the second active material layer both include a positive electrode active material, a conductive agent and a binder, the ratio of the content of the binder in the first active material layer to the content of the binder in the second active material layer is 1.1 to 1.5, the weight percentage of the binder in the second active material layer is 1% to 2%, and the negative electrode active material is selected from natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , a combination of one or more of Li-Al alloys.
2. The lithium ion battery according to claim 1, wherein The conductive agent in the first active material layer is selected from carbon nanotubes and conductive carbon black.
3. The lithium ion battery according to claim 1, wherein The binder is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and fluorinated olefin, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, fluorinated rubber, polyvinyl alcohol and combinations thereof.
4. The lithium ion battery according to claim 1, wherein: The bonding force between the first active material layer and the aluminum substrate is 80 N / m to 180 N / m, and the bonding force between the second active material layer and the first active material layer is 23 N / m to 130 N / m.
5. The lithium ion battery according to claim 1, wherein: The positive electrode active material in the first active material layer includes a combination of one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide; the positive electrode active material in the second active material layer includes a combination of one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate; and the conductive agent in the second active material layer is selected from conductive carbon black.
6. The lithium ion battery according to claim 1, wherein: The energy density of the lithium-ion battery is greater than 660 WH / L.
7. The lithium ion battery according to claim 1, wherein: The compaction density of the positive electrode sheet is 3.75 g / cc-4.05 g / cc.
Citation Information
Patent Citations
Lithium-ion secondary battery and preparation method for pole piece thereof
CN101969114A
Lithium ion secondary battery
JP2013062105A